A Chang'E-1 global catalog of lunar impact craters. (July 2015) - Wang, Jiao; Cheng, Weiming; Zhou, Chenghu
Abstract: Using Chang'E-1 images and a digital elevation model, we have compiled a global catalog of 106016 impact craters with diameters greater than 500 m. For all the craters, we integrated all the morphologic attributes available and examined the distribution of craters to identify and investigate potential spatial asymmetries. Highlights: Detected lunar impact craters with diameters more than 500 m using Chang'E-1 data in a hybrid method. Compiled a global catalog of 106016 impact craters with comprehensive morphometric parameters. Inspected the asymmetric spatial distribution of impact craters.